Development of neuroanesthesia laboratory model as a practicum learning media for students of STKA Poltekkes ministry of hospital Yogyakarta - Susilo, Catur Budi; Ermawan, Budhy; Pudjiati, Pudjiati (International journal of health sciences, 2022)
This study aims to develop a neuroanesthesia laboratory model and an appropriate learning device. This research method is development research with 4D design at the Health Polytechnic of the Ministry of Health Yogyakarta. The define step is by analyzing the superior curriculum, study program, material analysis and formulation of objectives, the design step by making a prototype lab with all the completeness of the instrument including learning guide devices. The development step is testing the contents of both the lab and manuals through a Focus Group Discussion of anesthesiologists and expert validators and all their input. The results of this study have produced three learning products: first, a learning syntax model for neuroanesthesia practice that is relevant to the achievement of student competencies. Second, the prototype model of the neuroanesthesia laboratory setting both pre, intra and post anesthesia. Third, the learning product is a guide to neuroanesthesia techniques and procedures for undergraduate students of applied nursing anesthesiology study program. The results of this study have produced three learning products.